Pembentukan Jiwa Entrepreneurship pada Siswa SMKN 1 Kraksaan Probolinggo Melalui Koperasi Krida Siswa - Ashari, Muhammad Hasyim; Ridwan, Mohammad Syahid (Welfare : Jurnal Pengabdian Masyarakat, 2025)
The instillation of entrepreneurial spirit in students of SMKN 1 Kraksaan Probolinggo is one of the efforts to equip them with entrepreneurial skills that can be applied in life. This community service activity is carried out through the management of the Krida Siswa Cooperative, aimed at providing practical experience in entrepreneurship, introducing cooperative management, and enhancing students' creativity and independence. The method used is Service Learning, which includes planning, training and mentoring in direct practice of cooperative's operations, as well as monitoring and evaluation. The results of this activity show an increase in students' understanding of entrepreneurial concepts, cooperative management, and decision-making in business. Additionally, this activity has successfully sparked students' interest in entrepreneurship in the future and strengthened the managerial skills of students at SMKN 1 Kraksaan Probolinggo.